Investigating Leptin Gene Variants and Methylation Status in Relation to Breastfeeding and Preventing Obesity - Ayse Kilic; Sacide Pehlivan; Muhammet Ali Varkal; Fatima Ceren Tuncel; Ibrahim Kandemir; Mustafa Ozcetin; Sükran Poyrazoglu; Asli Derya Kardelen; Irem Ozdemir; Ismail Yildiz (MDPI AG, 2024)
Objective: We investigated whether the results of leptin gene (LEP) 2548G/A (rs7799039) and leptin receptor gene (LEPR) 668 A/G (rs1137101) variants, as well as the methylation analysis of CpG regions at nucleotides −31 and −51 of the LEP gene, showed any differences between breastfed and non-breastfed children in this study. Materials and Methods: The cross-sectional study included 100 children aged 2-5 years who were attending nursery and kindergarten and had been accepted to the Department of General Paediatrics. Infants who were exclusively breastfed for the first six months after birth constituted the study group, and those who were not only breastfeed constituted the control group. Methylation percentages at CpG islands of the LEP gene were compared between exclusively breastfed and non-exclusively breastfed infants, and the statistical significance was analyzed by looking for changes in LEP −31 and −51 nt methylation and LEP 2548G/A ve LEPR 668 A/G variants. Results: Both groups were compared by feeding, and the association of LEPR and LEP gene polymorphisms and −51 nt and −31 nt methylations were analyzed. There were no significant differences between the groups regarding genotype and allele frequency for the LEPR 668 A/G, LEP 2548 G/A gene variant, −31 nt methylation, and −51 nt methylation status. Similarly, there was no significant difference in genotype and allele frequency for the LEPR 668 A/G gene variant in terms of duration of exclusive breastfeeding, total breastfeeding, body mass index, family obesity, and satiety status. However, maternal support from family elders and physical activity increased the 51 nt methylation, but this methylation was not significantly affected by BMI, age, or satiety status. Conclusions: Maternal support from family elders and physical activity were associated with increased 51 nt methylation, but this methylation was not significantly affected by BMI, age, or satiety status. However, there are not enough studies in this area to reach a definitive conclusion, and further research is needed.